MIND MAPPING STRATEGY: IS IT EFFECTIVE OR NOT TO IMPROVE THE STUDENTS’ ABILITY IN WRITING TOURISM BROCHURES? - Albert Efendi Pohan (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
The objective of this study is to find out whether Mind Mapping is effective or not in improving students’ ability in writing tourism brochures at SMA 20 Batam. This study is limited on writing tourism brochure for tenth grade students at SMA Negeri 20 Batam in Academic year 2017/2018. The study was designed by the writer by using true experimental design (pre-test and post-test control group). The population of the study were tenth grade students of SMA Negeri 20 Batam academic year 2017/2018. There were eight classes of tenth grade students with the total number 300 students. The samples of this study were two classes which consist of 30 students in experiment class and 30 students in control class. The instrument of this study was written test. The data analysis was used Independent Samples Test on IBM SPSS statistics 20 to perform T-test. The result showed that the Sig.(2-tailed) of students’ pre-test and post-test in experimental was 0.401 and standard significance level was 0.05. By comparing the Sig.(2-tailed) and standard significance level, it was known that Sig.(2-tailed) was bigger than standard significance level (0.401 0.05). It means there was no significant difference in writing tourism brochure before and after taught by using Mind Mapping in experimental class. Therefore, the alternative hypothesis (Ha) was rejected and the null hypothesis (Ho) was accepted. The conclusion of Mind Mapping was not given significant effect in improving students’ ability in writing tourism brochure.